Empyema and bacteremic pneumococcal pneumonia in children under five years of age - Maria Regina Alves Cardoso; Cristiana Maria Costa Nascimento-Carvalho; Fernando Ferrero; Eitan Naaman Berezin; Raul Ruvinsky; Clemax Couto Sant'Anna; Maria Cristina de Cunto Brandileone; Maria de Fatima Bazhuni Pombo March; Ruben Maggi; Jesus Feris-Iglesias; Yehuda Benguigui; Paulo Augusto Moreira Camargos (Jornal Brasileiro de Pneumologia, 2014)
We compared bacteremic pneumococcal pneumonia (BPP) and pneumococcal empyema (PE), in terms of clinical, radiological, and laboratory findings, in under-fives. A cross-sectional nested cohort study, involving under-fives (102 with PE and 128 with BPP), was conducted at 12 centers in Argentina, Brazil, and the Dominican Republic. Among those with PE, mean age was higher; disease duration was longer; and tachypnea, dyspnea, and high leukocyte counts were more common. Among those with BPP, fever and lethargy were more common. It seems that children with PE can be distinguished from those with BPP on the basis of clinical and laboratory findings. Because both conditions are associated with high rates of morbidity and mortality, prompt diagnosis is crucial.